The Influence of Awareness, Knowledge and Coretax on Taxpayer Compliance - Akhmad Akhmad; Yeni Elfiza Abbas (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
This study examines the influence of tax awareness, tax knowledge, and the Coretax system on taxpayer compliance among individual taxpayers in Jakarta, with education positioned as an antecedent factor influencing awareness, knowledge, and adaptation to digital tax administration. A quantitative explanatory approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through structured questionnaires distributed to individual taxpayers with experience using the Coretax system. The findings reveal that tax awareness and tax knowledge have positive and significant effects on taxpayer compliance, whereas the Coretax system does not yet exert a significant direct influence on compliance during its early implementation. Furthermore, education significantly enhances taxpayer awareness, tax knowledge, and Coretax adoption, although it does not directly affect taxpayer compliance. The study contributes to the integration of the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) by demonstrating that behavioral factors remain more influential than technological factors in explaining taxpayer compliance within a digital taxation environment. The findings also highlight the importance of strengthening taxpayer education, improving tax literacy, and providing continuous assistance to support the successful implementation of digital tax administration reforms.